Implementation of the Fuzzy Logic Controlled 31-Level Diode Switched Multilevel Inverter with Optimal Components for Solar PV-Fed System - Paneti Anjaneya Vara Prasad; C. Dhanamjayulu (International Transactions on Electrical Energy Systems)
This work presents a novel architecture for the 31-level asymmetrical DC voltage source configured diode switched multilevel inverter, which has a single phase and fewer components. Using asymmetric DC sources and an H-bridge, the proposed topology generates a maximum output voltage of 31 levels. This 31-level topology is suitable for both renewable energy source conversion (RES) and electric vehicle (EV) applications. This topology requires fewer total components, lower cost, and smaller size. Along with the numerous benefits of MLIs, reliability issues are critical due to the larger number of devices required to minimize THD. Several characteristics, such as total standing voltage (TSV), reliability, cost function (CF), efficiency, and overall power losses, are investigated for the developed 31-level MLIs. The TSV and CF of the proposed MLI are critical factors in demonstrating that the proposed topology is cost-effective when compared to other recent topologies. Many parameters are thoroughly compared and tabulated, as well as represented graphically. The suggested MLI has lower TSV and component demand. Total harmonic distortion complies with IEEE specifications. The reliability aspects were also calculated and validated. The proposed MLI is controlled by a fuzzy logis controller (FLC) to achieve efficient results. The topology is simulated in MATLAB/Simulink software under a variety of conditions and dynamic load changes, and a prototype with a dSPACE controller is also implemented.